Enhanced Thermal Stability and Energy Transfer by Crystal‐Field Engineering in a Garnet Phosphor for Thermometry and NIR‐LED. Issue 22 (21st August 2022) - Zhou, Luhui; Lyu, Zeyu; Sun, Dashuai; Shen, Sida; Tan, Taixing; Wang, Lixuan; Zhao, Hanwei; You, Hongpeng
Abstract: It is of significant importance to tailor the luminescent properties of Cr 3+ ions as efficient near‐infrared (NIR) emitter for extended optical applications. Here, crystal field engineering is explored to tailor the luminescent properties of a Cr 3+ ‐doped garnet, Lu2 Ca1 ‐ x Srx Al4 SiO12 ( x  = 0–1). As Ca 2+ is substituted by Sr 2+, the emission of Cr 3+ becomes sharper with longer lifetime, indicating that the 2 Eg → 4 A2g transition becomes dominant. More importantly, the thermal stability is greatly improved, as the emission intensity at 480 K increases from 83% to 111% of that at 300 K. Moreover, the efficiency of the energy transfer from the Cr 3+ to Yb 3+ /Nd 3+ increases from 60–70% to 80–90%. The intensity ratio of I 810 / I 706 from the Lu2 SrAl4 SiO12 :Cr 3+, Nd 3+ can be applied to thermometry, with the maximum relative sensitivity value of 1.43% K –1 at 303 K. Compared with the blue emission from light‐emitting diode (LED) chip, a clearer and more accurate imaging is established with NIR emission from Cr 3+ . Furthermore, the intensity ratio of the emissions from the Cr 3+ and Yb 3+ ions is applied to differentiate pork, chicken, and beef. These findings provide an avenue to optimize the thermal stability and energy transfer of Cr 3+ ‐activated NIR emitters for the applications in thermometry and NIR‐LED. Abstract : The thermal stability and energy transfer efficiency in the near‐infrared (NIR) phosphors, Lu2 Ca1 ‐ x Srx Al4 SiO12 :Cr 3+, Yb 3+ /Nd 3+, have been greatly enhanced by the crystal‐field engineering of Ca–Sr substitution. A sensitive thermometry with maximum relative sensitivity value of 1.43% K −1 is obtained. On the basis of the high‐performance NIR phosphors, the NIR‐LED applications in bio‐imaging and nondestructive analysis have been demonstrated.